1988
DOI: 10.1364/ol.13.000984
|View full text |Cite
|
Sign up to set email alerts
|

Tight focusing and blue shifting of millijoule femtosecond pulses from a conical axicon amplifier

Abstract: We focus millijoule femtosecond pulses to a spot radius of 2 microm after amplification free of phase-front distortion in a Nd:YAG-pumped conical axicon dye cell. Peak focal intensities reach 10(16) W/cm(2) , creating an intense spark that is caused by air breakdown at the focus. Intensity-dependent blue shifts of the pulse spectrum as large as 11 nm are observed as a result of temporally asymmetric self-phase modulation in the air-breakdown plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…(1). Because of the now reduced contrast between the guided and unguided portions of the pulse, the weak, ionization blueshifted photons [22] at the very front of the pulse are now visible.…”
mentioning
confidence: 99%
“…(1). Because of the now reduced contrast between the guided and unguided portions of the pulse, the weak, ionization blueshifted photons [22] at the very front of the pulse are now visible.…”
mentioning
confidence: 99%
“…Polycrystalline Fe and Al targets were illuminated by 0.62 mm dye laser pulses with peak focused intensity I # 10 15 W͞cm 2 . Although our system could produce shorter, more intense pulses [18], optimum peak-to-pedestal contrast (10 5 at 60.9 ps and 10 3 at 60.23 ps)-and minimum target surface preexpansion-was achieved with the system operating at 120 fs and I # 10 15 W͞cm 2 [19]. I (and thus x osc ) was calibrated by standard pulse energy and spot size measurements and cross-checked by immersing the target surface in ϳ1 atm He gas, which caused a sharp reflectivity drop and breakdown spark when I $ I thresh 1.2 6 0.1 3 10 15 W͞cm 2 , the ionization threshold of He [20].…”
mentioning
confidence: 99%
“…Wilks et al [2] have also deduced an interesting additional consequence; the appearance of a time independent residual magnetic field with the characteristic wavelength equal to the vacuum wavelength of the passing radiation. Recent theory and experiment have conclusively demonstrated that a powerful short laser pulse propagating in a gas can experience a strong frequency blueshift caused entirely by the plasma generated by the pulse itself [4].…”
mentioning
confidence: 99%